Respiratory effects of analgesia after cholecystectomy: comparison of continuous and intermittent papaveretum. Issue 6238 (16th August 1980) - Catling, J A; Pinto, D M; Jordan, C; Jones, J G
Abstract : Two methods of administering papaveretum for relieving postoperative pain were compared in two groups of patients who had undergone cholecystectomy. In one group a loading dose of papaveretum was administered by continuous intravenous infusion (1 mg/min) until the patient could breathe deeply without undue pain. Eight times this loading dose was given as a continuous intravenous infusion over the subsequent 48 hours. This regimen was compared with a conventional intermittent intramuscular dose (0.25 mg/kg at four hourly intervals as necessary) in a second group of patients. The intravenous regimen relieved pain better than the intramuscular regimen, which may have reflected the larger dose of papaveretum given to the intravenous group, but it was accompanied by a greater degree of respiratory depression and potentially life-threatening changes in respiratory pattern. These findings suggest that the fear which often accounts for inadequate postoperative pain relief-that larger dose of analgesics will cause respiratory complications-is well founded.